Thinking about the equal sign: What do students see about the equal sign? - Lia Ardiansari; Didi Suryadi; Dadan Dasari (Journal of Didactic Mathematics, 2022)
The equal sign seems to be interpreted differently by students depending on the learning experiences they have had in the early grades. In fact, the interpretation of the equal sign as a relational symbol does not seem easy or fast for many students to understand. This study aims to explore how students from elementary school to college students describe their understanding of the equal sign. The Qualitative Comparative Analysis can be used to analyze several cases in complex situations so that it fits the purpose of this study. The process of collecting data through the method of written assignments, semi-structured interviews, and documentation was carried out in one time period. This study involved 30 participants in Bandung, Indonesia. The results show that although there are substantial differences in viewing the equal sign, there are similarities in terms of dependence on computational methods in drawing conclusions. This is related to how their experience of number sentences in lower grades places more emphasis on rules than on the meaning of concepts.